THE SYSTEM OF CHECKS AND BALANCES IN IRELAND - Voichuk , Alina (Collection of scientific papers «ΛΌГOΣ», 2025)
The system of checks and balances in Ireland is a fundamental principle of the democratic system, which ensures a balance between the branches of government and prevents the concentration of powers within a single branch. The system of checks and balances in Ireland is implemented through clearly defined constitutional provisions governing the interaction between the President, the Dáil, the Government and the judiciary.